61 - GERIATRIC NURSING INTERVENTIONS TO FRAIL ELDERLY (Fiep Bulletin - online, 2011)
Descriptive study of type literature review, carried through Bibliographic survey on the theme of fragility in the elderly, in electronic databases LALCSH (Latin-American Literature and of Caribbean in Sciences of the Health) and BDN (Base of Data in Nurse). Were found, respectively, 355 and 102 articles, after application of the criteria for inclusion and exclusion, achieved a corpus of 95 studies. There was a predominance of the qualitative approach in the descriptor "geriatric nursing" and quantitative in descriptor "frail elderly" being identified several theoretical and methodological. The most studied objects were nurses and gerontology, followed hospital assistance for the elderly , elderly and the social coexistence , falls in the elderly and the elderly and ADL. Based on these results, we concluded that there is need to increase the production of knowledge in Nursing in Health Care of the Elderly, since, to give visibility to this thematic, it is necessary to recognize this specialty as a professional area acting.
Keywords: Geriatric Nursing; Frail Elderly; Nursing Assistance